Teaching Factory Model Using Flipped Classroom and Knowledge Management System Based in Improving 21st Century Competencies in Vocational High Schools - Vitriani Vitriani; Finanta Okmayura; Gunawan Ali; Robby Satria (STAI Hubbulwathan Duri, 2023)
The students in Vocational High Schools are demanded to have skills and competencies to face the world industry, but sadly many Vocational School Graduates have the incompatibility of skills and competencies, which seriously causes high unemployment rates. Therefore, an effective learning model needs to be implemented to overcome this problem. This research aims to produce a Teaching Factory Model Using Flipped Classroom and Knowledge Management System (KMS) Based. Providing a learning model that can be a solution to increase the competence of vocational students in meeting the needs of the industrial world and the business world in facing challenges in the Revolution 4.0 era. The research methodology used is Research and Development with ADDIE stages. This research produces a Model Teaching Factory based Flipped Classroom and Knowledge Management System. Based on the study results, the learning model teaching factory based Flipped Classroom and Knowledge Management System valid, practical and effective in Enhancing 21st Century Competencies in Vocational High Schools. The renewal of the model is designed to calibrate the Teaching Factory model based on Flipped Classroom and Knowledge Management System, a 21st century competency needed by the industrial world.